Price vs. quantity competition in a vertically related market - Maria Alipranti; Chrysovalantou Milliou; Emmanuel Petrakis (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
This paper demonstrates that the standard conclusions regarding the comparison of Cournot and Bertrand competition are reversed in a vertically related market with upstream monopoly and trading via two-part tariffs. In such a market, downstream Cournot competition yields higher output, lower wholesale prices, lower final prices, higher consumers' surplus, and higher total welfare than Bertrand competition.
Keywords: D43; L13; L14; 330; Cournot; Bertrand; vertical relations; two-part tariffs